2015
DOI: 10.1146/annurev-immunol-032414-112116
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress in Immunity

Abstract: Immune responses occur in the midst of a variety of cellular stresses that can severely perturb endoplasmic reticulum (ER) function. The unfolded protein response is a three-pronged signaling axis dedicated to preserving ER homeostasis. In this review, we highlight many important and emerging functional roles for ER stress in immunity, focusing on how the bidirectional cross talk between immunological processes and basic cell biology leads to pleiotropic signaling outcomes and enhanced sensitivity to inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
348
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(352 citation statements)
references
References 212 publications
(185 reference statements)
3
348
0
1
Order By: Relevance
“…Proteotoxic damage responses are aimed at repairing or eventually degrading unfolded nascent or mature proteins as a means to preserve essential cellular functions 53,54 . Proteotoxic damage responses can act as bona fide tissue damage control mechanisms, promoting the establishment of disease tolerance to bacterial infection 53,[55][56][57][58] ( Figure 2). Of note, proteotoxic damage responses are also involved in the regulation of immune-driven resistance mechanisms against intracellular bacteria and viruses, some of which evolved to modulate these responses as a strategy to repress host resistance to infection 53 59 .…”
Section: Damage Responses and Tissue Damage Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteotoxic damage responses are aimed at repairing or eventually degrading unfolded nascent or mature proteins as a means to preserve essential cellular functions 53,54 . Proteotoxic damage responses can act as bona fide tissue damage control mechanisms, promoting the establishment of disease tolerance to bacterial infection 53,[55][56][57][58] ( Figure 2). Of note, proteotoxic damage responses are also involved in the regulation of immune-driven resistance mechanisms against intracellular bacteria and viruses, some of which evolved to modulate these responses as a strategy to repress host resistance to infection 53 59 .…”
Section: Damage Responses and Tissue Damage Controlmentioning
confidence: 99%
“…aeruginosa infection in C. elegans 58 while preserving homeostatic control of microbiota interactions with host gut epithelia 53 . The DNA damage responses orchestrated by ATM 17 and by p53 165 confer tissue damage control and disease tolerance to pulmonary bacterial infections in mice.…”
Section: Box 3 Microbiota and Disease Tolerancementioning
confidence: 99%
“…[5][6][7][8][9][10] In addition to the induction of IFNs, viral infections also trigger ER stress response. [11][12][13][14][15] A best-studied stress-responsive signaling pathway is the UPR. The UPR induces transmembrane stress sensors, IRE1, ATF6, and PERK, that are localized in the ER.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is initiated by protein kinase RNA-like ER kinase (PERK). Activation of PERK contributes to the accumulation of activating transcription factor 4 (ATF4) (Bettigole and Glimcher, 2015;Sano and Reed, 2013), which upregulates ATF3 and CHOP expression. We checked the expression level of the CHOP-encoding gene ddit3 and found that, like atf3, ddit3 was upregulated in zar1 mutants (Fig.…”
Section: Loss Of Zar1 Triggers Er Stress and The Unfolded Protein Resmentioning
confidence: 99%